Antidepressant Effect of Blue Light on Depressive Phenotype in Light-Deprived Male Rats. Issue 12 (26th November 2020) - Meng, Qinghe; Jiang, Jianjun; Hou, Xiaohong; Jia, Lixia; Duan, Xiaoxiao; Zhou, Wenjuan; Zhang, Qi; Cheng, Zhiyuan; Wang, Siqi; Xiao, Qianqian; Wei, Xuetao; Hao, Weidong
Abstract: Blue light has been previously reported to play a salient role in the treatment of seasonal affective disorder. The present study aimed to investigate whether blue light had antidepressant effect on light-deprivation-induced depression model, and the underlying visual neural mechanism. Blue light mitigated depression-like behaviors induced by light deprivation as measured by elevated sucrose preference and reduced immobility time. Blue light enhanced melanopsin expression and light responses in the retina. We also found the upregulation of serotonin and brain derived neurotrophic factor expression in the c-fos-positive areas of rats treated with blue light compared with those maintained in darkness. The species gap between nocturnal albino (Sprague-Dawley rat) and diurnal pigmented animals (human) might have influenced extrapolating data to humans. Blue light has antidepressant effect on light-deprived Sprague-Dawley rats, which might be related to activating the serotonergic system and neurotrophic activity via the retinoraphe and retinoamygdala pathways. Blue light is the effective component of light therapy for treatment of depression.